Process Capability Model Based on COBIT 5 Assessments (Case Study) - Johanes Fernandes Andry (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
XYZ Company is Information and Communication Technology solutions provider in Jakarta. Started in 2003 as reseller product IT and development software customized, networking and other outsourcing project base. It has become imperative to strengthen IT governance and audit processes, to ensure the integrity of information systems. COBIT helps business and their IT achieves these, and builds a powerful, integrated framework for IT governance, control and audit processes. COBIT 5 is not only a cost-efficient approach, but also a conceptually easy framework for auditors to understand and communicate to the management. COBIT 5 moves away from the "maturity models" in COBIT 4.1, to Process Capability Model, they seek continuous improvement of business process. Assessing the value of the information and identifying the assets which support the business process. Assessment focused to domain Build Acquire and Implement (BAI). From the perspective of assessment activity, control classification by action is the most usefull conceptualization and within that context: preventive, detective, and corrective controls the most useful for analysis. Assessments of Process Capability Model based on COBIT 5 in domain BAI, average was at 2.4 (managed) until 3.0 (established).